The European Union and Cyprus: The Power of Attraction as a Solution to the Cyprus Issue - Christou, George (Journal on Ethnopolitics and Minority Issues in Europe, 2002)
Since the application of the government of the Republic of Cyprus was accepted by the European Union (EU) and accession negotiations began in March 1998, controversy has surrounded the extent to which the accession process could help or hinder a solution to the longstanding division on the island. The main purpose of this paper is to explore the extent to which EU accession and the 'power of attraction' can act as a catalyst for a solution to the Cyprus issue. The main argument is that despite much negative comment surrounding the accession process, portraying it as 'a catalyst for catastrophe' rather than solution, there are many positives to Cyprus' accession which, in the long-term, will be beneficial to all parties involved in the 'Cyprus dispute'-the Greek Cypriots, the Turkish-Cypriots and Turkey. Moreover, it is argued that the EU, in the form of enlargement and eventual membership for Cyprus and Turkey, can provide the necessary incentives and framework (economic, political, security) for a solution to the Cyprus issue.